Virtual Environments for People who Are Visually Impaired Integrated into an Orientation and Mobility Program. (January 2015) - Lahav, Orly; Schloerb, David W.; Srinivasan, Mandayam A.
Introduction: The BlindAid, a virtual system developed for orientation and mobility (O&M) training of people who are blind or have low vision, allows interaction with different virtual components (structures and objects) via auditory and haptic feedback. This research examined if and how the BlindAid that was integrated within an O&M training program could be of help when teaching those who are blind or visually impaired to develop O&M skills. Methods: Using qualitative and quantitative methods, this research focused on 16 participants during their O&M course, and studied virtual environment exploration and orientation tasks in virtual environments. Results: The encouraging results of the current study indicate the potential strengths of the BlindAid system as an O&M training device for visually impaired people. Discussion: Follow-up research evaluating transference of knowledge from virtual environments to real spaces could contribute to O&M training for people who are visually impaired. Implications for practitioners: BlindAid could play a central role in three potential applications: a training simulator for O&M, a diagnostic tool for O&M specialists to track and observe participants' spatial behavior, and a technique for advanced exploration of unknown spaces.